1978
DOI: 10.1021/ic50182a043
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and thermodynamic study of reactions of some substituted manganese(I) and manganese(II) tricarbonyl complexes using spectrophotometric and electrochemical techniques

Abstract: This is not true for Mo 3d, but there is a large error on the very weak Mo 3d5/2 shake-up peak (Figure lb).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 15 publications
3
22
0
Order By: Relevance
“…The kinetics and thermo- dynamics associated with the oxidative isomerisation of fac-[MnCI(CO),(dppm)] have been partially quantified, with the fac cation converting to the mer isomer via a non-dissociative twist mechanism. We have not quantified the processes involved for the conversion of (1) to (2), but the observed variation in the reversibility of the oxidation wave for (1) with the ligand L (see above) suggests qualitatively that the rate of isomerisation, kiso, of (1+) to (2+) increases in the order L = CN, py > Br, CNMe, NCMe, P(OPh), > NCS.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The kinetics and thermo- dynamics associated with the oxidative isomerisation of fac-[MnCI(CO),(dppm)] have been partially quantified, with the fac cation converting to the mer isomer via a non-dissociative twist mechanism. We have not quantified the processes involved for the conversion of (1) to (2), but the observed variation in the reversibility of the oxidation wave for (1) with the ligand L (see above) suggests qualitatively that the rate of isomerisation, kiso, of (1+) to (2+) increases in the order L = CN, py > Br, CNMe, NCMe, P(OPh), > NCS.…”
Section: Resultsmentioning
confidence: 97%
“…The bromide ligand is trans to CO, and the manganese has a distorted octahedral co-ordination geometry with the largest distortions due to the restricted bite of the chelating dppm ligand [ P-Mn-P 71.4( 1 )"I. The structure analysis has aided a brief discussion of the significance of the linear correlations between Eo and the ligand constant, P,, observed for both (1 ) and (2).…”
mentioning
confidence: 99%
“…[MnBr(CO) 3 (IMP)] (1). [MnBr(CO) 5 ] (1.1 mmol, 0.3 g) was combined with IMP (1.1 mmol, 0.2 g) in diethyl ether (20 mL) and refluxed under aerobic conditions for 4 h. 39 The product was formed in quantitative yield. 1 [MnBr(CO) 3 (TBIMP)] (4).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Importantly, despite uncertainties in the assignment of the spin state, the EPR result implies that even in the absence of any externally applied potential, the manganese(I) complex attached to the electrode surface in contact with an aqueous (electrolyte) solution phase can be oxidized to a Mn(II) complex upon photolysis. Furthermore, it can be noted that the EPR spectrum also is similar to that observed after chemical oxidation of fac -Mn(CO) 3 (η 2 -dpm)Cl. , The EPR spectra in Figure were obtained at 77 K. At ambient temperature (293 K), EPR spectra were barely detectable above background, but have the same basic features as those observed at 77 K.
5 EPR spectra obtained in the ex situ mode at 77 K after fac -Mn(CO) 3 (η 2 -dpm)Cl is attached to a graphite electrode (open circuit potential) and then placed in contact with 0.1 M NaCl aqueous electrolyte for 5 min: (lower curve) absence of light and (upper curve) presence of 300−450 nm UV/visible light (intensity, 10 mW cm -2 ).
…”
Section: Resultsmentioning
confidence: 53%
“…It is suggested that upon photolysis of the microcrystalline material, the manganese(I) species forms a charge-transfer excited state, which is then rapidly oxidized to a fac- manganese(II) cationic product that can then isomerize to the mer + form. From solution-phase studies, it is known that photolysis of fac -Mn(CO) 3 (η 2 -dpm)Cl induces isomerization to the mer form. , Thus, it is also possible that it is this mer isomer generated by photoisomerization that is in turn photooxidized directly to its mer cationic form. Presumably, reduction of water at the interface and transfer of chloride ion from the electrolyte to solid phases complete the photoredox reaction.…”
Section: Resultsmentioning
confidence: 99%